Entre unas palabras y unas cosas : La dimensión etnográfica del Atlas Lingüístico-Etnográfico de Colombia (ALEC) - Munévar Salazar, Alejandro; Bernal Chávez, Julio Alexander (Universidad Pedagógica y Tecnológica de Colombia, 2018)
Páginas: 20-35.